Bunga Kamboja pada Feminine Romantic Style - Resfi Novita Putri; Nofi Rahmanita; Desra Imelda; Mirda Aryadi (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
The work titled Plumeria in Feminine Romantic Style draws inspiration from the Plumeria flower (Plumeria alba), translating its essence into garments that embody a feminine, romantic aesthetic. This project serves as a platform to showcase and promote the Plumeria inspired designs to the public. The collection comprises a blouse, a skirt, a long dress, and a skirt with a trailing train. Plumeria motifs are incorporated into Tando Pusako batik a traditional textile from Mukomuko, Bengkulu to complement the garments. The color palette is derived directly from the Plumeria flower, featuring soft pastels such as muted yellow, white, soft green, and muted brown. For this final project, the creator presents three categories of fashion ready to wear, ready to wear deluxe, and haute couture. These are crafted using a blend of high-quality materials, specifically Yamaha silk satin and Tando Pusako batik. Corsage and beadwork techniques are employed to highlight garment details the corsage technique creates three dimensional accents that lend a luxurious feel to the outfits. The design process involved field exploration, a study of cultural heritage, and design development that aligns with current fashion trends while preserving traditional identity. This project serves not only as an artistic endeavor but also as a medium for cultural preservation, fostering appreciation for traditional textiles, and introducing cultural heritage into the modern fashion landscape. The collection was unveiled at a fashion show held at the Hoeridjah Adam Building at ISI Padangpanjang. It is hoped that this work will instill a sense of pride in the younger generation regarding the development of fashion rooted in local culture. The resulting pieces include the ready to wear outfit Rona Kamboja (Plumeria Hue), the ready to wear deluxe outfit Pesona Kamboja (Plumeria Charm), and the haute couture outfit Blooming Serenity.   Keywords: Frangipani Flower, Feminine Romantic Style, Batik Tando Pusako   Abstrak   Karya yang berjudul "Bunga Kamboja Pada Feminine Romantic Style" terinspirasi  dari bunga Kamboja ( plumeria alba)  ini diwujud dalam karya busana feminine romantic style. Karya ini juga  mengekspresikan bunga Kamboja ke dalam karya busana feminine romantic menjadi ajang pamer sekaligus mempromosikan kepada masyarakat. Busana Kamboja yang diwujudkan yaitu blus, rok, long dress serta slayer ekor rok. Bunga Kamboja diterapkan pada motif kain batik tando pusako khas Mukomuko Bengkulu untuk pendukung busana yang dibuat. Warna yang dipilih secara langsung di bunga Kamboja, warna pastel seperti kuning kalem, putih, hijau kalem,dan coklat kalem. Dalam  penciptaan karya tugas akhir ini, pengkarya menghadirkan tiga jenis busana ready to ewar, ready to wear deluxe, dan haute couture. Ketiganya diwujudkan melalui perpaduan bahan yang berkualitas yaitu satin yamaha silk dan batik  tando pusako. Untuk menampilkan detail busana yang dibuat dengan teknik korsase dan payet. Teknik korsase digunakan untuk menciptakan aksen tiga dimensi yang memberikan kesan mewah pada busana. Proses perancangan dimulai  dari eksplorasi lapangan, studi pusaka, dan pengembangan desain yang mengacu pada tren mode terkini namun tetap mempertahankan identitas tradisional. Penciptaan busana ini tidak hanya sebagai karya seni, tetapi juga sebagai media pelestarian budaya, peningkatan apresiasi terhadap kain tradisional, dan upaya dalam memperkenalkan warisan budaya ke ranah modern. Tahap penyajian karya dilakukan melalui pergelaran busana fashion show yang diselegarakan di Gedung Hoeridjah Adam ISI Padangpanjang. Karya ini diharapkan mampu menumbuhkan rasa bangga terhadap generasi muda dalam mengembangkan busana yang dilandasi budaya lokal. Hasil karya pada busana ready to wear dengan judul rona kamboja, busana ready to wear deluxe dengan judul pesona kamboja, dan busana haute couture dengan judul blooming serenety.  Kata Kunci : Bunga Kamboja, Feminine Romantic Style, batik tando pusako.